Comparative efficacy of ropivacaine and levobupivacaine in combined femoral and lateral femoral cutaneous nerve block with adjuvant magnesium for post-operative analgesia - Prakash Khairnar; Munisha Agarwal; Uttam Chandra Verma; Rakesh Kumar (Indian Journal of Anaesthesia, 2016)
Background and Aims: Patients with burns may require multiple surgeries, but poor general condition and underlying protein energy malnutrition make them unsuitable candidates for general or spinal anaesthesia. This study evaluated the role of magnesium sulphate as an adjuvant with levobupivacaine and ropivacaine used in combined femoral and lateral femoral cutaneous nerve (LFCN) blocks in burn patients with relative sparing of thigh portion. Methods: This prospective, randomised, double-blind study included 54 adult patients of 18-65 years age, undergoing split-thickness skin graft harvest from the thigh, allotted to three equal groups of 18 each. Group L patients received femoral nerve (FN) block with 15 mL of 0.5% levobupivacaine and 8 mL for LFCN block; Group LM patients received 14 mL of 0.5% levobupivacaine along with 1.0 mL of 15% magnesium sulphate for FN block, 7.5 mL of 0.5% levobupivacaine with 0.5 mL of 15% of magnesium sulphate to LFCN block and Group R patients received 15 mL of 0.5% ropivacaine for FN block and 8 mL of 0.5% ropivacaine for LFCN block. Time to block onset and complete surgical block, duration of analgesia, total analgesic dose and the overall analgesia satisfaction score were measured in the first 24 h post-operatively. Quantitative data were analysed with ANOVA and qualitative data subjected to Chi-square tests. Intergroup comparison was performed with independent t-test. Results: The duration of post-operative analgesia did not differ with the addition of magnesium (P = 0.610). Time to onset of the block was significantly decreased with the addition of magnesium (P = 0.0341), but time to complete surgical block onset was similar across the groups. Conclusion: Both ropivacaine and levobupivacaine have good perioperative analgesic efficacy. Magnesium as an analgesia adjuvant with levobupivacaine does not prolong the duration of post-operative analgesia.